Crystal structure of di-μ-isobutyrato-κ(4) O:O′-bis[cis-dichlorido(dimethyl sulfoxide-κS)rhenium(III)] - Golichenko, Alexander A. (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, [Re(2)(C(3)H(7)COO)(2)Cl(4){(CH(3))(2)SO}(2)], comprises binuclear complex molecules [Re—Re = 2.24502 (13) Å] involving cis-oriented double carboxylate bridges, four equatorial chloride ions and two weakly bonded O atoms from dimethyl sulfoxide ligands in the axial positions at the Re(III) atoms. In the crystal, molecules are linked into corrugated layers parallel to (101) by very weak C—H⋯Cl and C—H⋯O hydrogen-bonding interactions. C—H⋯Cl hydrogen bonding provides the links between layers to consolidate a three-dimensional framework.